Multiple organ dysfunction syndrome, an unusual complication of heroin intoxication: a case report and review of literature - Feng, Gang (Int J Clin Exp Pathol, 2015)
Multiple organ dysfunction syndrome (MODS) has rarely been described in patients with heroin intoxication. Here, we report a rare case of MODS involving six organs, due to heroin intoxication. The patient was a 32-year-old Chinese man with severe heroin intoxication complicated by acute pulmonary edema and respiratory insufficiency, shock, myocardial damage and cardiac insufficiency, rhabdomyolysis and acute renal insufficiency, acute liver injury and hepatic insufficiency, toxic leukoencephalopathy, and hypoglycemia. He managed to survive and was discharged after 10 weeks of intensive care. The possible pathogenesis and therapeutic measures of MODS induced by heroin intoxication and some suggestions for preventing and treating severe complications of heroin intoxication, based on clinical evidence and the pertinent literature, are discussed in this report.